Invariant HVC size in female canaries singing under testosterone: Unlocking function through neural differentiation, not growth - Shouwen Ma; Carolina Frankl-Vilches; Manfred Gahr (Proceedings of the National Academy of Sciences, 2025)
Testosterone administration to nonsinging adult female canaries induces song, making this a model for behavioral plasticity and its underlying neural mechanisms in vertebrates. The song control nucleus HVC is traditionally believed to undergo a substantial size change when transitioning from a nonfunctional to a functional (song-producing) state. Using 2-photon in vivo imaging, we tracked the spatial distribution and anatomical properties of HVC neurons over several weeks of testosterone-induced song development. Surprisingly, despite ultrastructural changes of HVC neurons, testosterone did neither alter neuronal spacing nor HVC size. Instead, spatial transcriptomics revealed that testosterone modulates gene networks throughout HVC, aligning transcriptomic profiles between its peripheral and central HVC regions in singing birds, thereby mimicking the histological appearance of an enlarging HVC. Our results demonstrate that changes in HVC size in adults reflect phenotypic changes in neurons within a stable framework. Importantly, the nonfunctional state is not associated with a reduced brain area volume, preserving HVC’s capacity for functional differentiation throughout life.